Prevalence and morphometry of Eimeria spp in guinea pigs from Chota, Cajamarca - Torrel Pajares, Severino (2023)
This study determine the prevalence of Eimeria spp and performs the morphometric study of the oocysts found in the faeces of guinea pigs (Cavia porcellus) from commercial family-rearing farms in the district of Chota, Cajamarca, Peru. The study was conducted between August and October 2014. In total, 285 faecal samples were obtained regardless of sex, age and type of guinea pigs in eight communities. The samples were processed using the Sheather technique and the morphometric study of the oocysts was carried out by microscopic observation at 40X using a micrometric eyepiece with a correction factor of 1.64. Oocyst sporulation was induced with 2.5% potassium dichromate. The prevalence of Eimeria spp was 25%. The average of ovoid-shaped oocysts was 17.46 µm long and 17.25 µm wide and for ellipsoidal oocysts it was 23.40 µm long and 17.8 µm wide. The morphometric characteristics indicate that it would be Eimeria caviae.